Feedback loop between hypoxia and energy metabolic reprogramming aggravates the radioresistance of cancer cells - Zheng Shi; Cuilan Hu; Xiaogang Zheng; Chao Sun; Qiang Li (Experimental Hematology & Oncology, 2024)
Abstract Radiotherapy is one of the mainstream approaches for cancer treatment, although the clinical outcomes are limited due to the radioresistance of tumor cells. Hypoxia and metabolic reprogramming are the hallmarks of tumor initiation and progression and are closely linked to radioresistance. Inside a tumor, the rate of angiogenesis lags behind cell proliferation, and the underdevelopment and abnormal functions of blood vessels in some loci result in oxygen deficiency in cancer cells, i.e., hypoxia. This prevents radiation from effectively eliminating the hypoxic cancer cells. Cancer cells switch to glycolysis as the main source of energy, a phenomenon known as the Warburg effect, to sustain their rapid proliferation rates. Therefore, pathways involved in metabolic reprogramming and hypoxia-induced radioresistance are promising intervention targets for cancer treatment. In this review, we discussed the mechanisms and pathways underlying radioresistance due to hypoxia and metabolic reprogramming in detail, including DNA repair, role of cancer stem cells, oxidative stress relief, autophagy regulation, angiogenesis and immune escape. In addition, we proposed the existence of a feedback loop between energy metabolic reprogramming and hypoxia, which is associated with the development and exacerbation of radioresistance in tumors. Simultaneous blockade of this feedback loop and other tumor-specific targets can be an effective approach to overcome radioresistance of cancer cells. This comprehensive overview provides new insights into the mechanisms underlying tumor radiosensitivity and progression.